Effect of individualized social activities on quality of life among older adults with mild to moderate cognitive impairment in a geriatric psychiatry facility. (3rd March 2016) - DiNapoli, Elizabeth A.; Scogin, Forrest; Bryant, Ami N.; Sebastian, Sabin; Mundy, Michael J.
Abstract : Objectives : The study examined the effect of an individualized social activities intervention (ISAI) on quality of life among older adults with mild to moderate cognitive impairment in a geriatric psychiatry facility. Method : This randomized control trial consisted of 52 older adults ( M = 70.63, SD = 5.62) with mild to moderate cognitive impairment in a geriatric inpatient psychiatry facility. A 2 (group condition) × 2 (time of measurement) design was used to compare the control (treatment-as-usual) and intervention (treatment-as-usual plus ISAI) conditions at pre- and post-treatment. ISAI consisted of 30- to 60-minute sessions for up to 15 consecutive days. The Dementia Quality of Life instrument and Neurobehavioral Rating Scale – Revised were used to examine quality of life and behavioral and psychological symptoms of dementia at pre- and post-treatment. Results : Intent-to-treat analyses indicated a significant time × group condition interaction on quality of life, with this effect remaining when only completer data were included. There was no evidence of a significant treatment effect on behavioral and psychological symptoms of dementia. Conclusion : Findings suggest that individualized social activities are a promising treatment for cognitively impaired geriatric inpatients.